First Record of the Parasitic Nematode Anisakis simplex in the Intestine and Gonads of Dentex macrophthamus off Syrian Marine Waters - Masri, Mai; Saad, Adib A.; Sabour, Waad; Layka, Taghrid (Iraqi Journal of Aquaculture, 2023)
This study aimed to investigate the infection of internal parasites of Dentex macrophthalmus in Syrian marine coastal waters. A total of 409 individuals were collected from Ras Al-Basit in the north to Tartus in the south, from the following research stations: Ras Al-Basit, different areas along the Lattakia beach, Jableh, and Tartous, during the period from January 2019 to December 2020. The internal organs (stomach, intestine, and body cavity) of all fish specimens were examined to detect infection with internal parasites. The third-stage larvae of the parasite Anisakis simplex, which belongs to the nematode worms, was isolated from the stomach and gonad walls of D. macrophthalmus. The number of fish infected with this worm reached 53 out of 409 fish individuals studied, with an infection rate of 12.96% and an infection intensity of 2.70 parasites per fish. This study represents the first record of Anisakis simplex isolated from the abdominal cavity of D. macrophthalmus in Syrian marine waters.